From Collective Ritual to Individual Distress: Representations of Wine Culture in Works Nominated for and Awarded the Večernica Prize (1997–2025) - Bale, Norma (Trideset let literarne nagrade večernica, 2026)
The article examines the occurrence and function of wine motifs in selected nominated and award-winning works for the Večernica Award in the period 1997–2025. It proceeds from the assumption that, in Slovenian children’s and young adult literature, wine does not appear merely as a realistic or folkloric background element, but as a multilayered cultural, identity-related, and problem-oriented motif. Drawing on qualitative content, thematic, discourse, comparative, and multimodal analysis, the article investigates how literary works represent wine as an element of cultural heritage, a symbol of regional and social identity, and a motif of social belonging, growing up, initiation, and intergenerational relations, while also functioning as a problem-oriented motif associated with intoxication, alcoholism, family distress, and social insecurity. The analysis encompasses poetry, prose, and multimodal works, and compares representations of wine according to literary genre, target age group, and the period in which the works were produced. The article demonstrates a shift from a traditionally self-evident representation of wine towards a more reflective, ambivalent, and socially critical treatment of alcohol in more recent works.